Development of the anti-gp120 antibody response during seroconversion to human immunodeficiency virus type 1. - Moore, J P (1994)
We have studied the development of the antibody response to the surface glycoprotein gp120 of human immunodeficiency virus type 1 in three individuals who presented with primary human immunodeficiency virus type 1 infection syndrome. Serum anti-gp120 antibodies were first detected 4 to 23 days after presentation, after p24 antigen and infectious-virus titers in the peripheral blood had declined manyfold from their highest values. Whether anti-gp120 antibodies present at undetectable levels are involved in clearance of viremia remains unresolved. Among the earliest detectable anti-gp120 antibodies were those to conformationally sensitive epitopes; these antibodies were able to block the binding of gp120 monomers to soluble CD4 or to a human monoclonal antibody to a discontinuous epitope overlapping the CD4-binding site. Some of these antibodies were type specific to a degree, in that they were more effective at blocking ligand binding to autologous gp120 than to heterologous gp120. However, the appearance of these antibodies did not correlate with that of antibodies able to neutralize the autologous virus in vitro by a peripheral blood mononuclear cell-based assay. Antibodies to the V3 loop were detected at about the same time as, or slightly later than, those to the CD4-binding site. There was a weak correlation between the presence of antibodies to the V3 loop and autologous virus-neutralizing activity in two of three individuals studied. However, serum from the third individual contained V3 antibodies but lacked the ability to neutralize the autologous virus in vitro, even immediately after seroconversion. Thus, no simple, universal correlate of autologous virus-neutralizing activity in a peripheral blood mononuclear cell-based assay is apparent from in vitro assays that rely on detecting antibody interactions with monomeric gp120 or fragments thereof.